Analisis Sosiolinguistik Campur Kode dan Alih Kode dalam Dialog Film Pendek Centang biru - Melly Destryani Utami; Falina Noor Amalia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Code mixing and code switching are increasingly prevalent phenomena in audiovisual media, particularly in short films that depict the communication patterns of young people in bilingual environments. This study aims to analyze the forms, types, and functions of code mixing and code switching found in the dialogue of the short film Centang Biru. The research problem focuses on how language mixing and switching are employed in the film’s dialogue, as well as the contextual and functional aspects underlying their use. This study adopts a descriptive qualitative approach, with data collected through observation and note-taking by repeatedly examining the film’s dialogue. The analysis process involves transcribing the dialogue, classifying instances of code mixing and code switching, and interpreting their functions based on the context of utterance. The findings reveal 13 instances of language alternation, consisting of 6 cases of external code switching and 8 instances of code mixing in the form of words, phrases, clauses, and repetition. Code mixing most frequently appears at the word and phrase levels, while code switching occurs through complete shifts between Indonesian and English. The results indicate that code mixing serves to enhance expression and social intimacy, whereas code switching functions to emphasize meaning and convey deeper emotional expression. This study is expected to contribute to sociolinguistic research, particularly in understanding language use in contemporary short film media